The Effect Of Propolis Extract From Trigona Spp. On Vascular Inflammatory Mediators And Its Molecular Mechanism In TNF-Alpha-Stimulated Endothelial Cells - Asem, NorNaimah (2019)
Propolis is one of the bee products which contained multiple chemical compounds, namely polyphenols, waxes, steroids and terpenoids. Its contents may be influenced by the plant sources, geographical area as well as the bee species. A wide array of natural products have been used as anti-inflammatory and healing agents, with propolis being a remarkable option. Therefore, the objective of this study is to examine the phytochemical properties of the selected propolis extracts and its effects on the expression of adhesion molecules, as well as the molecular mechanisms involved, particularly the investigations on the nuclear factor-kappa B (NF-ĸB) signalling pathways in cultured endothelial cell. In the present study, the phytochemical screening of ethanolic extract of propolis (EEP) from local stingless bee species namely Tetrigona apicalis, Geniotrigona thoracica and Heterotrigona itama were investigated using high performance liquid chromatography (HPLC) and gas chromatography-mass spectrometry (GC-MS) analysis. The total phenolic and flavonoid contents, and antioxidant activities which include 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) assay were explored.